2020
DOI: 10.1037/prj0000366
|View full text |Cite
|
Sign up to set email alerts
|

A short history of individual placement and support in Norway.

Abstract: Objective: Norway is a high-income and high-cost society with a generous welfare system, and has the largest mental health-related unemployment gap of the OECD countries. The aim of the current paper was to present a short history of Individual Placement and Support (IPS) services to increase work participation in Norway. Method: We provide a narrative overview of the developments and research on IPS in Norway, from the introduction of supported employment to recent and ongoing randomized controlled trials (RC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…In Norway, recent central political guidelines from the Ministry of Health and Care Services (Helse- og omsorgsdepartementet), have placed emphasis on developing more patient-centred care [ 19 ], consistent with requests from user organizations [ 20 ]. In the Norwegian national guidelines on assessment and treatment of persons with psychoses (2013), a recovery approach is emphasized as a general principle for good practice [ 21 ], and recent years have seen an increase in implementation of development recovery-oriented practices in Norway such as Illness Management and Recovery (IMR) [ 22 ] ACT/FACT –teams [ 23 ] and Individual Placement and Support (IPS) [ 24 ]. A previous study showed that a great majority of Norwegian service users with psychosis reported that support for personal recovery were important for them (article in press).…”
Section: Introductionmentioning
confidence: 99%
“…In Norway, recent central political guidelines from the Ministry of Health and Care Services (Helse- og omsorgsdepartementet), have placed emphasis on developing more patient-centred care [ 19 ], consistent with requests from user organizations [ 20 ]. In the Norwegian national guidelines on assessment and treatment of persons with psychoses (2013), a recovery approach is emphasized as a general principle for good practice [ 21 ], and recent years have seen an increase in implementation of development recovery-oriented practices in Norway such as Illness Management and Recovery (IMR) [ 22 ] ACT/FACT –teams [ 23 ] and Individual Placement and Support (IPS) [ 24 ]. A previous study showed that a great majority of Norwegian service users with psychosis reported that support for personal recovery were important for them (article in press).…”
Section: Introductionmentioning
confidence: 99%
“…The social workers' lack of knowledge and general confusion with the terminology raises the question how the implementation of EBP should best be carried out in the social sector. While EBP and ESTs such as Multisystem Treatment and Parent Management Training and Individual Placement and Support are being put into practice in the Norwegian social sector (Angel, 2003;Patras & Klest, 2016;Sveinsdottir et al, 2019), it is evident that the facilitated knowledge transfer between academia and the practice field is not reaching the practitioners. Further research should be done to bridge the gap in knowledge transfer between academia and practitioners in order to facilitate a better framework for understanding and utilizing EBP in practice.…”
Section: Resultsmentioning
confidence: 99%
“…In child welfare services, empirically supported treatments (ESTs) such as Multisystem Treatment and Parent Management Training are being put into practice (Angel, 2003;Patras & Klest, 2016). In social services, Individual Placement and Support are gaining popularity as a method to increase work integration in Norway (Sveinsdottir et al, 2019).…”
mentioning
confidence: 99%
“…Implementation of IPS requires policy accommodations to the health and labour services at a local, as well as governmental level [ 19 ]. Our study took place in a Norwegian context where national policy mandates widespread implementation of IPS [ 33 , 34 ] and IPS has systematically been studied in Norwegian trials since 2012 [ 35 ]. Norway is a high-income society, characterised by a generous welfare system and a low general unemployment rate [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Health and social services are rooted in two different sectors, regulated through different legislation and funded separately. The Norwegian mental health services provide community- based and specialised, hospital care [ 35 ]. For health services, local provision is influenced by governmental authorities through legislation, but local authorities are free to organise and arrange services to meet local conditions [ 38 ].…”
Section: Introductionmentioning
confidence: 99%